Managing Water-Ecosystem-Food Nexus using participatory approaches: insights from an innovative methodological approach developed in two Mediterranean areas - Malamataris, Dimitrios; Pisinaras, Vassilios; Pagano, Alessandro; Baratella, Valentina; Vanino, Silvia; Bea, Manuel; Babakos, Konstantinos; Chatzi, Anna; Fabiani, Stefano; Giordano, Raffaele; Kafkias, Petros; López-Moya, Estrella; et al. (Frontiers in Water, 2025)
The formulation of effective policies to address both the present allocation and future conservation of natural resources in an integrated way remains an essential and challenging task. In this regard, managing the Nexus is increasingly seen as a priority in resource governance. Nature-based Solutions (NbS) are gradually being advocated to enhance sustainable and resilient Nexus management efforts. Designing and planning NbS tailored to local contexts requires a thorough understanding of the specific challenges and perspectives, as well as the divergent perspectives among stakeholders. This paper presents and analyses an effective stakeholder engagement strategy, based on the Learning & Action Alliances (LAA) scheme and aimed at identifying Water-Ecosystems-Food (WEF) Nexus challenges and selecting NbS in two case studies in the Mediterranean area (Greece and Italy). In total, 60 stakeholders were engaged in more than 40 events (workshops, seminars, open days, field trips etc.), while 25 individual interviews were also conducted. By fostering collaboration and stakeholder ownership, the methodology provided actionable insights and promoted context-specific solutions. The stakeholders proposed 24 NbSs in the Italian case study, most of which were related to agricultural landscape management, while in the Greek case study, 2 of the 4 top-ranked measures were NbSs. The findings underline the importance of participatory approaches and transdisciplinary tools in addressing Nexus challenges, offering a replicable framework for sustainable resource management in resource-stressed regions.